Antioxidant responses of triangle sail mussel Hyriopsis cumingii exposed to harmful algae Microcystis aeruginosa and hypoxia. (November 2015) - Hu, Menghong; Wu, Fangli; Yuan, Mingzhe; Li, Qiongzhen; Gu, Yedan; Wang, Youji; Liu, Qigen
Highlights: The combined effects of toxic cyanobacteria and hypoxia on mussels were determined. Interactive effects of cyanobacteria and hypoxia on biomarkers were observed. Toxic algae plays more important role on haemolymph response than that of hypoxia. Toxic M. aeruginosa or hypoxia exposure history shows latent effects on mussels. Abstract: Bloom forming algae and hypoxia are considered to be two main co-occurred stressors associated with eutrophication. The aim of this study was to evaluate the interactive effects of harmful algae Microcystis aeruginosa and hypoxia on an ecologically important mussel species inhabiting lakes and reservoirs, the triangle sail mussel Hyriopsis cumingii, which is generally considered as a bio-management tool for eutrophication. A set of antioxidant enzymes involved in immune defence mechanisms and detoxification processes, i.e. glutathione-S-transferases (GST), glutathione (GSH), superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPX), lysozyme (LZM) in mussel haemolymph were analyzed during 14 days exposure along with 7 days depuration duration period. GST, GSH, SOD, GPX and LZM were elevated by toxic M. aeruginosa exposure, while CAT activities were inhibited by such exposure. Hypoxia influenced the immune mechanisms through the activation of GSH and GPX, and the inhibition of SOD, CAT, and LZM activities. Meanwhile, some interactive effects of M. aeruginosa, hypoxia and time were observed. Independently of the presence or absence of hypoxia, toxic algal exposure generally increased the five tested enzyme activities of haemolymph, except CAT. Although half of microcystin could be eliminated after 7 days depuration, toxic M. aeruginosa or hypoxia exposure history showed some latent effects on most parameters. These results revealed that toxic algae play an important role on haemolymph parameters alterations and its toxic effects could be affected by hypoxia. Although the microcystin depuration rate of H. cumingii is quick, toxic M. aeruginosa and/or hypoxia exposure history influenced its immunological mechanism recovery.